Pengetahuan Masyarakat Usia Produktif tentang Dampak Mengkonsumsi Minuman Berenergi pada Organ Ginjal - Tanoto, Wahyu (Universitas Muhammadiyah Klaten, 2023)
Productive age people are people who are in the age range of 15-64 years who have many activities and targets that must be achieved, coupled with the demands of work that require more energy instantly by consuming energy drinks without knowing the impact of energy drinks on the kidneys. The purpose of this study was to determine the knowledge of the productive age community about the impact of consuming energy drinks on the kidneys in Putuk Kulon Hamlet, Ngluyu Village, Ngluyu District, Nganjuk Regency. Descriptive research design, population of 304 respondents, sample of 30 respondents, using a purposive sampling technique, questionnaire sheet research instruments, the research was conducted on March 16 - April 16 2023. The research variable was knowledge of the productive age community about the impact of consuming energy drinks on the kidneys. The data were analyzed using the percentage formula and the results were interpreted quantitatively. The results of the study were obtained from 30 respondents, half of the respondents had sufficient knowledge of 15 respondents (50%), almost half of the respondents had less knowledge of 8 respondents (27%), and a small proportion of respondents had good knowledge of 7 respondents (23%). This is influenced by several factors, namely age and marital status so that respondents are expected to have and add insight about knowledge of the impact of consuming energy drinks on the kidneys. Health workers are expected to provide regular health counseling for the community.